Composition and sources of fatty alcohols in estuarine sediments of Sungai Kapar - Norfariza Humrawali,; Yeoh, Lee Kwan; Mohd Talib Latif,; Masni Mohd Ali, (Universiti Kebangsaan Malaysia, 2010)
A total of 13 fatty alcohols (C12- C24) including six branched compounds have been identified in seven surface sediment samples taken from Sungai Kapar, Selangor using computerized gas chromatography-mass spectrometry (GC-MS). Generally 65% of total fatty alcohols determined were short chain compounds (C12- C20) derived from marine organisms, 14% were long chained compounds (C21- C24) input of terrestrial plants and the rest were branched compounds from bacterial activity. C16 compound dominated all the sampling stations with concentrations ranged from 29.69 to 164.35 μgg-1 dry weight which constitute 32% of total fatty alcohols. Short chain/long chain fatty alcohols ratio [Σ(C12- C20)/Σ(C21- C22)] of each sampling stations had the value >1; indicating high content of short chain compounds from marine sources. Meanwhile, Alcohol Source Index (ASI) calculated using C22/C14 and C22/C16 ratios. C22/C14 ratio showed that stations Kp1, Kp2, Kp5 and Kp6 had a value >1 indicating the amount of C22 was higher than C14. Ratio of C22/C16 showed that all the sampling stations dominated by C16 compared to C22. The estuary of Sungai Kapar, Selangor was dominated by short chain fatty alcohols (C12- C20) especially C16 compound rather than long chain fatty alcohol (C21- C24).